2022
DOI: 10.3389/fncel.2022.878673
|View full text |Cite|
|
Sign up to set email alerts
|

TAT-HSP27 Peptide Improves Neurologic Deficits via Reducing Apoptosis After Experimental Subarachnoid Hemorrhage

Abstract: Cell apoptosis plays an important role in early brain injury (EBI) after subarachnoid hemorrhage (SAH). Heat shock protein 27 (HSP27), a member of the small heat shock protein (HSP) family, is induced by various stress factors and exerts protective role on cells. However, the role of HSP27 in brain injury after SAH needs to be further clarified. Here, we reported that HSP27 level of cerebrospinal fluid (CSF) is increased obviously at day 1 in patients with aneurysmal SAH (aSAH) and related to the grades of Hun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…injection, which was performed as previously described. 35 In brief, rats following SAH were treated with a single i.c.v. injection (0.8 mm posterior, 1.2 mm lateral, and 3.8 mm depth) of RAH (5 μL, 50 μM; HY-15947A, MedChemExpress) or vehicle (5 μL, saline) with a 10 μL Hamilton syringe on a stereotaxic apparatus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…injection, which was performed as previously described. 35 In brief, rats following SAH were treated with a single i.c.v. injection (0.8 mm posterior, 1.2 mm lateral, and 3.8 mm depth) of RAH (5 μL, 50 μM; HY-15947A, MedChemExpress) or vehicle (5 μL, saline) with a 10 μL Hamilton syringe on a stereotaxic apparatus.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, RAH was administered by an intracerebroventricular (i.c.v.) injection, which was performed as previously described . In brief, rats following SAH were treated with a single i.c.v.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, TAT-HSPB8 was also proven to inhibit oxidative stress-induced apoptosis in hippocampal neuronal cells [49]. Furthermore, TAT-HSPB1 65-90 peptide attenuates neurological deficits and cortical apoptosis after experimental subarachnoid hemorrhage (SAH) [216]. Surprisingly, a study showed that the TAT-HSPB1 12-35 peptide induces lysosomal membrane permeabilization and the release of cathepsin D from lysosomes after entering clear cell renal cell carcinoma cells, resulting in apoptosis and inhibition of proliferation, which indicates that TAT-HSPB1 12-35 is a potential therapeutic agent for renal cancer [217].…”
Section: Shsps and Diseasementioning
confidence: 99%
“…The intracellular function of the HSP27 chaperone is regulated by phosphorylation and dephosphorylation in large aggregates that modulate the assembly of an ATP-independent network. As a chaperone, HSP27 is involved in DNA stabilization, supports antioxidant responses and also acts as an anti-apoptotic factor (92)(93)(94). Extracellular release of HSP27 from tissues where blood vessels are affected by atherosclerosis may result from cellular injury or occur in association with secretory lysosomes or exosomes.…”
Section: Features Of the Induction Of Small Atp-independent Hsps In M...mentioning
confidence: 99%